POTENSI LIMBAH CANGKANG KERANG SEBAGAI KATALIS HETEROGEN UNTUK PEMBUATAN BIODIESEL - Sebayang, Abdi Hanra; Pulungan, Muhammad Anhar; Siahaan, Sihar; Benu, Siti Maretia; Ibrahim, Husin; Siregar, Munawar Alfansury; Silitonga, Arridina Susan (Jurnal Rekayasa Mesin, 2024)
Biodiesel is a potential energy source that has attracted attention recently because it can be produced from renewable energy sources and produces low pollutants. Biodiesel is produced by transesterifying edible or non-edible vegetable oils using a catalyst. Homogeneous catalytic processes have disadvantages, such as the catalyst residue cannot be reused. Therefore, heterogeneous or solid catalysts are used, which can be easily separated from the reaction mixture by filtration and reused. A waste cockle shell can be used as a green base catalyst to synthesize waste cooking oil into methyl ester (WCME). The free fatty acid content of used cooking oil (2.19% wt.) was initially reduced to 0.11% wt., using a methanol-oil ratio of 6:1, waste cockle shell 2% wt., reaction time 60 minutes and temperature 60 oC. The effectiveness of the developed waste cockle shell contains high CaO. The results of this study indicated the potential of clam waste cockle shells and used cooking oil as a source of raw materials available in the community for biodiesel production.